Protective effect of Centella asiatica extract and powder on oxidative stress in rats - Hussin, Mahanom; Abdul Hamid, Azizah; Mohamad, Suhaila; Saari, Nazamid; Ismail, Maznah; Bejo, Mohd Hair (Elsevier, 2007)
The effect of Centella asiatica extract and powder in reducing oxidative stress in SpraqueDawley rats was evaluated. Lipid peroxidation was monitored by measuring malonaldehyde (MDA) level in blood. Activities of free radical-scavenging enzymes (superoxide dismutase and catalase) were determined using H2O2 decomposition and nitrobluetetrazolium reduction, respectively. Results showed that administration of H2O2 (0.1%) in drinking water of the rats, for 25 weeks, increased the malonaldehyde levels in erythrocytes of all the rats. However, rats receiving C. asiatica extract, powder and a-tocopherol had lower MDA levels than did the other rats, which indicates, decrease lipid peroxidation in these rats. Increase in catalase activity of the rats appears to be a response to H2O2 accumulation. The decrease in the activity of superoxide dismutase in C. asiatica- and a-tocopherol supplemented rats suggested a lower requirement for the enzyme and this indicates the protective effect of the plant in combating oxidative stress undergone by the rats. Results revealed that C. asiatica extract and powder may ameliorate H2O2-induced oxidative stress by decreasing lipid peroxidation via alteration of the antioxidant defence system of the rats.